2021
DOI: 10.3390/plants10030598
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rising Temperature in the Deposition Patterns of Bioactive Compounds in Field Grown Food Barley Grains

Abstract: High temperatures at the end of the season are frequent under Mediterranean conditions, affecting final grain quality. This study determined the deposition patterns throughout grain filling of dry matter, dietary fiber, phenolic compounds and antioxidant capacity for four barley genotypes under two contrasting temperatures. Deposition pattern for dietary fiber followed that of grain weight. Genotypic differences for duration were more significant than for rate. Anthocyanins followed a second-degree polynomial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…The results of ANOVA in this investigation indicated that both genotype and environment had a highly significant effect on all the traits examined. These findings were in agreement with those previously reported [ 27 ]. Such findings reveal that different genetic makeup of these barley genotypes can have varying inherent characteristics that affect their performance.…”
Section: Discussionsupporting
confidence: 94%
“…The results of ANOVA in this investigation indicated that both genotype and environment had a highly significant effect on all the traits examined. These findings were in agreement with those previously reported [ 27 ]. Such findings reveal that different genetic makeup of these barley genotypes can have varying inherent characteristics that affect their performance.…”
Section: Discussionsupporting
confidence: 94%
“…Kohyama et al [45] associated this reduction, occurring just before harvest, in purple hull-less varieties with processes such as degradation, diacylation, or insolubilization of anthocyanins. Bustos et al [46] reported a similar pattern in total anthocyanins in purple wheat, while Martínez-Subirà et al [20] observed the same trend barley genotypes. In both cases, the peak content of anthocyanins was reached at physiological maturity, followed by a significant decrease until harvest.…”
Section: Anthocyaninsmentioning
confidence: 77%
“…Previous researchers found that immature corn seeds possess high concentrations of reducing sugars, high protein contents with biological activity, and higher antioxidant activity than mature grains [19]. For barley, previous studies showed that total phenolic content gradually decreases throughout grain development, accompanied by a decline in antioxidant capacity [20]. However, comprehensive investigations into the dynamic changes of specific PCs such as phenolic acids, flavan-3-ols, flavones, and anthocyanins, and their corresponding antioxidant activities during the barley grain development are lacking.…”
mentioning
confidence: 99%
“…Biscuits containing different proportions of whole flour and pearling fractions from a purple hull-less barley genotype showed high in vitro antioxidant capacity [103]. Interestingly, genotypic differences influence the content of bioactive compounds more than the environment, and heat stress at the end of the growing season increased the phenolic compounds and their antioxidant capacity [104].…”
Section: Barleymentioning
confidence: 99%